Giant magnetic splitting inducing near-unity valley polarization in van der Waals heterostructures. Issue 1 (December 2017) - Nagler, Philipp; Ballottin, Mariana; Mitioglu, Anatolie; Mooshammer, Fabian; Paradiso, Nicola; Strunk, Christoph; Huber, Rupert; Chernikov, Alexey; Christianen, Peter; Schüller, Christian; Korn, Tobias
Abstract Monolayers of semiconducting transition metal dichalcogenides exhibit intriguing fundamental physics of strongly coupled spin and valley degrees of freedom for charge carriers. While the possibility of exploiting these properties for information processing stimulated concerted research activities towards the concept of valleytronics, maintaining control over spin–valley polarization proved challenging in individual monolayers. A promising alternative route explores type II band alignment in artificial van der Waals heterostructures. The resulting formation of interlayer excitons combines the advantages of long carrier lifetimes and spin–valley locking. Here, we demonstrate artificial design of a two-dimensional heterostructure enabling intervalley transitions that are not accessible in monolayer systems. The resulting giant effectiveg factor of −15 for interlayer excitons induces near-unity valley polarization via valley-selective energetic splitting in high magnetic fields, even after nonselective excitation. Our results highlight the potential to deterministically engineer novel valley properties in van der Waals heterostructures using crystallographic alignment. In transition metal dichalcogenide monolayers, the spin and valley degrees of freedom are strongly coupled. Here, the authors engineer a WSe2 /MoSe2 heterostructure in which inter-valley transitions of interlayer excitons exhibit a giant splitting and near-unity polarization in a magnetic field.